The Layer 2 Network Security at SMK Negeri 1 Rantau Alai using DHCP Snooping - Rahmat Novrianda D; Rasmila Rasmila (Universitas Islam Sultan Agung, 2020)
SMK Negeri 1 Rantau Alai is located at Ogan Ilir Regency, South Sumatera Province. In this Vocational High School (SMK), there are two majors namely Computer and Network Engineering (TKJ) and Software Engineering (RPL). SMK Negeri 1 Rantau Alai already has a computer network that used to communicate all users for file sharing called Local Area Network (LAN). It has been connected to the internet, but does not have a network security system so it`s very vulnerable to hacker intrusion who can do cyber crime. Therefore in this research, researcher built the network security on layer 2 Open System Interconnection (OSI) by utilizing DHCP Snooping technology to avoid cyber crime such as loss of important data from SMK Negeri 1 Rantau Alai database server. To implement DHCP Snooping, researcher need a routerboard Mikrotik device and also a switch that is one of hardware needed on the Data Link Layer. Besides that, Winbox and Putty software are also needed to help in the overall configuration of this research. The results obtained after DHCP snooping configuration done is the ability to recover IP addresse when converted to Fake IP will be able to return to its original IP address and limit the number of users who can access the internet at SMK 1 Rantau Alai Keywords: LAN, DHCP Snooping, Switch, Winbox, Putty